Resource management under endogenous risk of expropriation (2018)
This paper explores how the dynamic management of a non-renewable resource is affected by an endogenous (i.e., mitigable) risk of expropriation. The time at risk increases with the value of the resource in the ground and decreases with the cost of expropriating the resource. When the risk of expropriation is internalized by the legitimate owner, in the absence of capacity constraints, the resource is depleted faster than it is socially optimal. Interestingly, a marginal improvement in the protection of property rights exacerbates the over-extraction of the resource. In the presence of endogenous capacity constraints, and when property rights are imperfectly protected, both under- and over-extraction are possible. If property rights are relatively strong the resource owner under-invests in extraction capacity and depletes the resource below the socially optimal rate. If property rights are relatively weak the owner over-invests and the resource is over-extracted. © 2017 Elsevier B.V.